Remittances of Algerian workers abroad -Wasted wealth- - Benzeghioua Mohamed (Journal of North African Economies, 2025)
Remittances from workers abroad constitute an important source of cash flows for receiving countries. As they have had a positive impact on economic growth in many developing countries, although the impact of remittances from Algerian workers abroad did not have a significant impact on the Algerian economy, since these remittances were not exploited. In the Important productive sectors, but in terms of financial returns, it has remained the second largest source of hard currency in Algeria after the hydrocarbons sector for many decades, and this is what makes us remember it, which is the need for Algeria to pay attention to this important wealth for the Algerian economy.